ConBr, a lectin from Canavalia brasiliensis seeds, modulates signaling pathways and increases BDNF expression probably via a glycosylated target. Issue 12 (December 2014) - Rieger, Débora K.; Cunha, Rodrigo M. S.; Lopes, Mark William; Costa, Ana Paula; Budni, Josiani; Rodrigues, Ana Lúcia S.; Walz, Roger; Teixeira, Edson H.; Nascimento, Kyria S.; Cavada, Benildo S.; Leal, Rodrigo B.
<x xml:space="preserve">Abstract</x> In the central nervous system, many receptors, ion channels and neurotransmitter transporters are glycoproteins, where the glycan chains are modulator elements. Lectins are proteins, which recognize and bind carbohydrate complexes. We have previously shown that ConBr, a lectin purified from Canavalia brasiliensis seeds, produced antidepressant‐like effect and blocked hippocampal neurotoxicity induced by quinolinic acid and glutamate. Noteworthy, all these effects occurred in a dependence of its carbohydrate recognition domain. Therefore, the present study was undertaken in order to elucidate intracellular signaling pathways regulated by ConBr that may be potentially associated with the antidepressant and neuroprotective effects previously reported to be dependent on carbohydrate interaction. ConBr (10 µg/site) was injected into the ventricle (i.c.v.) of mice, and the hippocampi were removed 0.5, 1, 3, 6, 8, 12, 18, and 24 h after treatment. Our results showed that in the period of 0.5–3 h, ConBr induced activation of the protein kinases Akt, ERK1, and PKA. Furthermore, the phosphorylation of CREB‐Ser133 was stimulated by ConBr (1–6 h), while brain‐derived neurotrophic factor (BDNF) mRNA was increased at 12 h and BDNF protein at 18–24 h. Our data suggest that an early activation of protein kinases may trigger CREB‐dependent BDNF transcription, resulting in a subsequent increase of BDNF protein in response to ConBr. Later, increment of Akt phosphorylation was observed 24 h after ConBr administration, possibly due to BDNF/TrkB‐dependent activation of Akt. Our findings indicate that ConBr is a multifunctional molecule capable to activate signaling pathways involved in neuroplasticity and neuroprotection. Copyright © 2014 John Wiley & Sons, Ltd.